Research on coordinated control method of hybrid energy storage systems connected traction power supply system based on PFTD - HUANG Jun (机车电传动)
Electrified railways using single-phase power-frequency AC systems have the advantages of pollution-free operation and high transportation efficiency. However, the current traction power supply systems face prominent challenges related to negative sequence and inefficient utilization of regenerative braking energy. Therefore, this paper proposed a power flow transfer topology for integrated hybrid energy storage systems. The analysis focused on the topology structure of the power flow transfer device (PFTD) for integrated hybrid energy storage, and delved into peak shaving, valley filling, regenerative braking, and in-phase operation modes, along with corresponding energy management strategies. Moreover, a coordinated control strategy was proposed, to reduce system losses, as well as further improve the utilization of regenerative braking energy and the control accuracy of peak shaving and valley filling. Additionally, a passive nonlinear current controller was introduced to improve the control response speed of converters. Finally, the simulation results indicate that the proposed system fully utilize the regenerative braking energy of the traction power supply system, improve the flexibility of energy flow in the system, and solved concerns related to negative sequence in the traction power supply system.